2009
DOI: 10.2175/193864709793954006
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Solar Drying Technology to Trinidad and Tobago

Abstract: A review of the existing solids management practices in Trinidad and Tobago and experience elsewhere defined the future needs and identified solar drying as a preferred technology for the subject project. Upon analysis of the local conditions, it was calculated that approximately 19 MJ/m 2 (1886 kWh/m²) of solar radiation, at 30ºC annual average temperature and 80% relative humidity level is appropriate at the project site and that these parameters are adequate for the solar dryer application. The estimated 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Initial work performed at the OSP indicated that the interior of the chamber could get up to 100ºF during daylight hours, with significant heat losses overnight. Evaporation rates for greenhouse applications range from 1 kg water/m 2 -day (Bux and Bauman 2003) to 2.2 kg water/m 2 -day (Mangat et al 2009). Success of the pilot unit was therefore measured against these industry figures, while also acknowledging that the chamber was not constructed as an ideal solar dryer would be.…”
Section: Resultsmentioning
confidence: 99%
“…Initial work performed at the OSP indicated that the interior of the chamber could get up to 100ºF during daylight hours, with significant heat losses overnight. Evaporation rates for greenhouse applications range from 1 kg water/m 2 -day (Bux and Bauman 2003) to 2.2 kg water/m 2 -day (Mangat et al 2009). Success of the pilot unit was therefore measured against these industry figures, while also acknowledging that the chamber was not constructed as an ideal solar dryer would be.…”
Section: Resultsmentioning
confidence: 99%
“…Evaporation rates (daily averages) for greenhouse applications range from 1 kg/m 2 -day (Bux and Bauman 2003) to 2.2 kg/m 2 -day [6]. Success of the pilot unit was therefore measured against these industry figures, while also acknowledging that the chamber was not constructed as an ideal solar dryer would be.…”
Section: Discussionmentioning
confidence: 99%
“…Success of the pilot unit was therefore measured against these industry figures, while also acknowledging that the chamber was not constructed as an ideal solar dryer would be. For example, a more demonstration scale model would be better insulated to protect against However the limitations of the experiment as conducted, the evaporation rate for the mixed sample is 121% higher than current state of the art for solar biosolids dryers [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, 90% and 70% DS are achieved by thermal dryers and GSDs, respectively (Flaga, 2007;Mangat et al, 2009;Bux and Baumann, 2003;Ritterbusch and Bux, 2012). Therefore, a GSD should be supported with auxiliary heat in order to reach higher DS (i.e.…”
Section: Cost Functionsmentioning
confidence: 99%